2019
DOI: 10.1515/jbcpp-2019-0121
|View full text |Cite
|
Sign up to set email alerts
|

Trema orientalis (Linn.) leaves promotes anticancer activity in Ehrlich ascites carcinoma (EAC) in Swiss albino mice

Abstract: BackgroundThe in vivo anticancer effect of the Trema orientalis leaves crude methanol extract (TLME) was screened against Ehrlich ascites carcinoma (EAC) in Swiss albino mice.Materials and methodsThe cytotoxic activity of TLME was determined in vitro by the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. The growth inhibitory activity and morphological alterations were determined by the hemocytometer counting of the EAC cells using trypan blue dye. The apoptotic cells were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Following the methodology outlined in a prior investigation with slight changes, an ethanol extract of Christella dentata 's aerial parts (EECD) was prepared. 27 A total of 100 grams of powdered plant material were split into four separate 500 mL conical flasks. To each flask, 100 mL of ethanol was introduced, and the flasks were then kept within a shaking incubator (JSSI-300T, JSR, South Korea), undergoing agitation at 250 rpm for 72 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Following the methodology outlined in a prior investigation with slight changes, an ethanol extract of Christella dentata 's aerial parts (EECD) was prepared. 27 A total of 100 grams of powdered plant material were split into four separate 500 mL conical flasks. To each flask, 100 mL of ethanol was introduced, and the flasks were then kept within a shaking incubator (JSSI-300T, JSR, South Korea), undergoing agitation at 250 rpm for 72 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that HCT116 cells significantly declined, about 98 % at 7.5 μg/mL after fourteen days of incubation and exhibited the strongest clonogenic activity [ 71 ]. Similarly, Kabir et al [ 72 ] studied the anticancer potential of T. orientale methanolic leaf extracts in Swiss albino mice against Ehrlich ascites carcinoma (EAC). The animals were transplanted with EAC and treated for six days with the crude extract, intraperitoneal EAC cells were then collected, harvested and counted by hemocytometer.…”
Section: Pharmacological Activities/studiesmentioning
confidence: 99%
“…They are still a huge source of prominent and effective bioactive compounds that are capable of being employed as medications right away [ 2 ]. There are numerous examples of plant-based medications, like antimicrobial as nicotine, antioxidant as nordihydroguaiaretic acid (NDGA), anticancer as vinblastine, bleomycin, paclitaxin, and taxol, and anti-inflammatory as aescin and capsaicin, cardiotonic as acetyldigoxin, and antiparkinsonism as l -dopa, etc [ 1 , 3 ]. Their use is promoted in the Ayurvedic, Unani, Siddha, Homeopathic, and other frameworks of medication [ 1 ].…”
Section: Introductionmentioning
confidence: 99%